Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Ali, Usman; Holthaus, Martin; Meier, Torsten (Physical Review Research)
Keywords: General Physics and Astronomy

Chirped Bloch-harmonic oscillations in a parametrically forced optical lattice - Meier, Torsten

Accelerating the analysis of optical quantum systems using the Koopman operator - Peitz, Sebastian; Hunstig, Anna; Rose, Hendrik; Meier, Torsten
The prediction of photon echoes is an important technique for gaining an understanding of optical quantum systems. However, this requires a large number of simulations with varying parameters and/or input pulses, which renders numerical studies expensive. This article investigates how we can use data-driven surrogate models based on the Koopman operator to accelerate this process. In order to be successful, we require a model that is accurate over a large number of time steps. To this end, we employ a bilinear Koopman model using extended dynamic mode decomposition and simulate the optical Bloch equations for an ensemble of inhomogeneously broadened two-level systems. Such systems are well suited to describe the excitation of excitonic resonances in semiconductor nanostructures, for example, ensembles of semiconductor quantum dots. We perform a detailed study on the required number of system simulations such that the resulting data-driven Koopman model is sufficiently accurate for a wide range of parameter settings. We analyze the L2 error and the relative error of the photon echo peak and investigate how the control positions relate to the stabilization. After proper training, the dynamics of the quantum ensemble can be predicted accurately and numerically very efficiently by our methods.

Manipulation of nonautonomous nonlinear wave solutions of the generalized coupled Gross–Pitaevskii equations with spin–orbit interaction and weak Raman couplings - Belobo, D. Belobo; Meier, Torsten (Results in Physics)
Keywords: General Physics and Astronomy

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Revealing the nonadiabatic tunneling dynamics in solid-state high harmonic generation - Zuo, Ruixin; Song, Xiaohong; Ben, Shuai; Meier, Torsten; Yang, Weifeng (Physical Review Research)
Keywords: General Physics and Astronomy

Theoretical analysis of four-wave mixing on semiconductor quantum dot ensembles with quantum light - Rose, Hendrik; Grisard, S.; Trifonov, A. V.; Reichhardt, R.; Reichelt, Matthias; Bayer, M.; Akimov, I. A.; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of an ensemble of semiconductor quantum dots is analyzed by wave-mixing processes, where we focus on four-wave mixing with two incident pulses. Wave-mixing experiments are often described with semiclassical models, where the light is modeled classically and the material quantum mechanically. Here, however, we use a fully quantized model, where the light is given by a quantum state of light. Quantum light involves more degrees of freedom than classical light as e.g., its photon statistics and quantum correlations, which is a promising resource for quantum devices, such as quantum memories. The light-matter interaction is treated with a Jaynes-Cummings type model and the quantum field is given by a single mode since the quantum dots are embedded in a microcavity. We present numerical simulations of the four-wave-mixing response of a homogeneous system for pulse sequences and find a significant dependence of the result on the photon statistics of the incident pulses. The model constitutes a problem with a large state space which arises from the frequency distribution of the transition energies of the inhomogeneously broadened quantum dot ensemble that is coupled with a quantum light mode. Here we approximate the dynamics by summing over individual quantum dot-microcavity systems. Photon echoes arising from the excitation with different quantum states of light are simulated and compared.

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Gain recovery dynamics in active type-II semiconductor heterostructures - Meier, Torsten; Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Hader, J.; Moloney, J.V.; et al. (Applied Physics Letters)

Experimental studies of the excitonic nonlinear response of GaAs-based type-I and type-II quantum well structures interacting with optical and terahertz fields - Meier, Torsten; Stein, M.; Schäfer, F.; Anders, D.; Littmann, J. H.; Fey, M.; Trautmann, Alexander; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Fuchs, C.; Volz, K.; et al. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons is investigated experimentally using polarization resolved four wave mixing, optical-pump optical-probe, and optical-pump Terahertz-probe spectroscopy. The four-wave mixing data reveal clear signatures of coherent biexcitons which concur with straight-forward polarization selection rules at the Γ point. The type-I samples show the well-established time-domain beating signatures in the transients as well as the corresponding spectral signatures clearly. The latter are also present in type-II samples; however, the smaller exciton and biexciton binding energies in these structures infer longer beating times which, in turn, are accompanied by faster dephasing of the type-II exciton coherences. Furthermore, the THz absorption following spectrally narrow, picosecond excitation at energies in the vicinity of the 1s exciton resonance are discussed. Here, the optical signatures yield the well-established redshifts and blueshifts for the appropriate polarization geometries in type-I quantum well samples also termed “AC Stark Effect”. The THz probe reveals intriguing spectral features which can be ascribed to coherent negative absorption following an excitation into a virtual state for an excitation below the 1s exciton resonance. Furthermore, the scattering and ionization of excitons is discussed for several excitation geometries yielding control rules for elastic and inelastic quasiparticle collisions.

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Meier, Torsten; Trautmann, Alexander; Stein, M.; Schäfer, F.; Anders, D.; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Chatterjee, S. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons excited by optical fields is analyzed by numerical solutions of the semiconductor Bloch equations. Differential absorption spectra are computed for resonant pumping at the exciton resonance and the dependence of the absorption changes on the polarization directions of the pump and probe pulses is investigated. Coherent biexcitonic many-body correlations are included in our approach up to third-order in the optical fields. Results are presented for spatially-direct type-I and spatiallyindirect type-II quantum well systems. Due to the spatial inhomogeneity, in type-II structures a finite coupling between excitons of opposite spins exists already on the Hartree-Fock level and contributes to the absorption changes for the case of opposite circularly polarized pump and probe pulses.

Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells - Meier, Torsten; Ngo, C.; Priyadarshi, S.; Duc, H. T.; Bieler, M. (Ultrafast Phenomena and Nanophotonics XXVII)
Anomalous currents refer to electronic currents that flow perpendicularly to the direction of the accelerating electric field. Such anomalous currents can be generated when Terahertz fields are applied after an optical interband excitation of GaAs quantum wells. The underlying processes are investigated by numerical solutions of the semiconductor Bloch equations in the length gauge. Excitonic effects are included by treating the manybody Coulomb interaction in time-dependent Hartree-Fock approximation and additionally also carrier-phonon scattering processes are considered. The band structure and matrix elements are obtained from a 14-band k · p model within the envelope function approximation. The random phase factors of the matrix elements that appear due to the separate numerical diagonalization at each k-point are treated by applying a smooth gauge transformation. We present the macroscopic Berry curvature and anomalous current transients with and without excitonic effects. It is demonstrated that the resonant optical excitation of excitonic resonances can significantly enhance the Berry curvature and the anomalous currents.

Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

Multiple Rabi rotations of trions in InGaAs quantum dots observed by photon echo spectroscopy with spatially shaped laser pulses - Grisard, S.; Rose, Hendrik; Trifonov, A. V.; Reichhardt, R.; Reiter, D. E.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Meier, Torsten; Akimov, I. A. (Physical Review B)

Microscopic simulations of high harmonic generation from semiconductors - Trautmann, Alexander; Zuo, Ruixin; Wang, Guifang; Hannes, Wolf-Rüdiger; Yang, Shidong; Thong, Le Huu; Ngo, Cong; Steiner, Johannes; Ciappina, Marcelo; Reichelt, Matthias; Duc, Huynh Thanh; Song, Xiaohong; et al. (Ultrafast Phenomena and Nanophotonics XXVI)

Theoretical analysis of correlations between two quantum fields exciting a three-level system using the cluster-expansion approach - Rose, Hendrik; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina (Ultrafast Phenomena and Nanophotonics XXVI)

Steady states of Λ-type three-level systems excited by quantum light with various photon statistics in lossy cavities - Rose, Hendrik; Tikhonova, O V; Meier, Torsten; Sharapova, Polina (New Journal of Physics)
Abstract The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high- Q cavities which strongly enhance the light–matter coupling. Cavities with low Q -factors are generally given less attention due to their high losses that quickly destroy quantum systems. However, bad cavities can be utilized for several applications, where lower Q -factors are required, e.g., to increase the spectral width of the cavity mode. In this work, we demonstrate that low- Q cavities can be beneficial for preparing specific electronic steady states when certain quantum states of light are applied. We investigate the interaction between quantum light with various statistics and matter represented by a Λ-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We show that cavity losses lead to non-trivial electronic steady states that can be controlled by the loss rate and the initial statistics of the quantum fields. We discuss the mechanism of the formation of such steady states on the basis of the equations of motion and present both analytical expressions and numerical simulations for such steady states.
Keywords: General Physics and Astronomy

Super-Bloch oscillations with parametric modulation of a parabolic trap - Meier, Torsten; Ali, Usman (Condensed Matter)

Coherent contributions to population dynamics in a semiconductor microcavity - Paul, J.; Rose, Hendrik; Swagel, E.; Meier, Torsten; Wahlstrand, J. K.; Bristow, A. D. (Physical Review B)